The Problem of World Outlook Compatibility in the Process of Communication - Vardumyan, Atom (Journal of Sociology: Bulletin of Yerevan University, 2015)
Any communication, regardless of nature and communicative aspect, supposes an interaction which, first and foremost, is reflected in human worldview, in attitudinal and value- determination systems in particular. Since it is not possible to achieve absolute ideological similarity as well as equivalency of interests, goals, and means of conflict resolution, it can be considered that there exists, in the communicative mode of interaction, a certain extent of contradiction which is implicitly or explicitly expressed in human perception, assessment and response mechanisms. It is the study of these mechanisms that rhetorics, as a system of theoretical and pragmatic tools and methods to achieve a most productive communication and ideological “reconciliation”, focuses. Apart from processing technical-technological devices to carry out debates and discussions, it aims at revealing certain factors conditioning a person’s inner identity and self-determination - significant moral, psychological and value orientations and various expressions of reservedness, biased mistrust and disrespect (in the communication process in particular). In addition, rhetorics offers ways to overcome and “neutralize” the above-mentioned problems in a most expedient manner.
Keywords: communication, contradiction, conflict resolution, perception, assessment and response mechanisms, rhetoric